Cultivating Morality Through Daily Al-Ma’thurat Recitation: Evidence from an Indonesian Islamic Boarding School - Asma Dzatin Nathaqain; Meti Fatimah; Dwi Santosa Pambudi (Walidem Institute and Publishing, 2025)
Objective: This study aims to examine the effect of the implementation of routine dhikr Al-Ma'surat in the morning and evening on the morals of students in grade 7 H at the Tahfidzul Qur'an Abi-Ummi Boyolali Islamic Boarding School. Theoretical framework: This research is on the importance of dhikr in the spiritual development and character formation of students, assuming that consistent worship practices can make a positive contribution to moral development. Literature review: this research includes studies related to dhikr, strengthening the character of students, and the role of the pesantren environment in shaping personality and morals. Methods: This study uses a quantitative method with a causal approach, where data is collected through a questionnaire that measures the implementation of Al-Ma'surat dhikr and documentation of students' moral values from the report card. Results: The results of the study showed that most of the students had a good category in the implementation of dhikr and their morals, but the results of the Product-Moment correlation test showed a very low and insignificant relationship (r = 0.017) between the implementation of dhikr Al-Ma'surat and the morals of the students. Implications: This research highlights the need for a more integrated dhikr development strategy and the strengthening of the pesantren environment that is more conducive to shaping the morals of students as a whole. Novelty: this research lies in the finding that although the dhikr of Al-Ma'surat is considered important, in practice it has not had a significant influence on the morals of the students, thus opening up opportunities to explore other factors that are more dominant in character formation.